(untitled) (Marketing Journal, 2025)
This article examines the processes of bioproduct production in various regions of Uzbekistan, the current state of the sector, and its economic efficiency. Based on an analysis of the agro-climatic conditions of the regions, the availability of production resources, and market demand for bioproducts, the possibilities for their cultivation are assessed. The results of the analysis reveal the economic potential and development prospects of the bioproduct sector.